2010
DOI: 10.1667/rr1661.1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Dependence of Ionizing Radiation-Induced DNA Deletions and Antioxidant Radioprotection inSaccharomyces cerevisiae

Abstract: The yeast DEL assay is an effective method for measuring intrachromosomal recombination events resulting in DNA deletions that when occurring in mammalian cells are often associated with genomic instability and carcinogenesis. Here we used the DEL assay to measure γ-ray-induced DNA deletions throughout different phases of yeast culture growth. Whereas yeast survival differed by only up to twofold throughout the yeast growth phase, proliferating cells in lag and early exponential growth phases were tenfold more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…A high percentage of cells were in the S/G2 phase of the cell cycle (70%) 24 h after the start of the experiment. Initial cultures at time zero were comprised predominantly (>90%) of G1/G0-phase cells, which agrees with literature data on S. cerevisiae ( Hafer et al, 2010 ). From the nanomechanical point of view, the oscillatory behavior of non-budding and budding yeast cells is expected to be different because of the difference in the mass of single cells in the G1/G0 phase (one cell) and in S/G2 phase (two new cells).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A high percentage of cells were in the S/G2 phase of the cell cycle (70%) 24 h after the start of the experiment. Initial cultures at time zero were comprised predominantly (>90%) of G1/G0-phase cells, which agrees with literature data on S. cerevisiae ( Hafer et al, 2010 ). From the nanomechanical point of view, the oscillatory behavior of non-budding and budding yeast cells is expected to be different because of the difference in the mass of single cells in the G1/G0 phase (one cell) and in S/G2 phase (two new cells).…”
Section: Resultssupporting
confidence: 91%
“…In the later stages of the cell cycle, yeast cells are most sensitive to the formation of homologous DNA deletion. It was shown that for S. cerevisiae within the first 30 h after X-ray irradiation, the magnitude of radiation-induced DNA deletions correlated positively with the fraction of cells in the S/G2 phase ( Hafer et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specific gene expression patterns of high-LET CI-irradiated Saccharomyces cerevisiae show that the DNA damage and oxidative lesions induced by CI can elicit broad cellular responses, including checkpoint pathway activation, cell cycle arrest, DNA repair, and oxidative stress response activation [ 5 ]. Simultaneously, the nature of the acute DNA damage induced by irradiation as well as the subsequent cellular responses and radioprotective processes depend on a variety of factors, including radiation quality, dose rate, cell type, cell cycle, and growth period [ 6 , 7 ]. Research into the molecular mechanisms of the effects of IR on organisms has been focused on complex, irreparable, clustered DNA damage and the changes in single or multiple DNA bases [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…MC cells are very slow-growing compared with the other murine and human cell lines in our study, which may explain the low level of γ-H2AX at 2 Gy, because slow-growing cells are less sensitive to radiation 51 than are rapidly proliferating cells. 52 , 53 This implies that MC cells are resistant to DNA damage at low radiation doses but are radiosensitive at higher doses, because robust γ-H2AX levels were detected at 8 Gy.…”
Section: Resultsmentioning
confidence: 99%